AN ANALYSIS OF APPRECIATIVE INTELLIGENCE TO TIME MANAGEMENT ON SUCCESSFUL MILLENNIALS AS THE CULINARY BUSINESS OWNER IN BANDUNG - Pratiwi, Risa
The data of the Ministry of Cooperatives & SME at the end of 2015 showed that culinary business has the largest contribution to GDP with the amount of Rp209 trillion or 32.5 percent, followed by fashion Rp182 trillion and handicraft Rp93 trillion. The owner of successful culinary business are mostly millennials. There must be some factors which influence those people to be success in business and one of them is leadership. Leadership related to Appreciative Intelligence which is the ability of controlling the environment, including their time management. The purpose of this study is to analyze how Appreciative Intelligence (AQ) playing role in the process of time management routines in millennial generation as business owner that generate business profits which tend to increase over time. Afterwards the findings will be used as a basic indicator in increasing the awareness of business owner’s AQ to the optimal level of time management. The results of this study are expected to be used by business owners in order to manage time effectively in starting and developing a business. This research is qualitative research conducted to explore objective of the study. To collect the data, the author conducted semi-structured interview method. The purposeful sampling conducted on this research. In this research, the research objects are the Millennials CEO of culinary business which business has a rapid growth and exists or established in Bandung. All of the interview was about 12 structured questions which are inspired from the book of Appreciative Intelligence (Thatchenkery and Metzker, 2002) and were recorded for transcription purposes. The three components of Appreciative Intelligence are not independent but strongly supporting, strengthen, and create an easiness for each other as it is a step by step of Appreciative Intelligence. The research findings of Appreciative Intelligence indicate that this ability leads to commitment, consistency, and encouragement to survive which require productivity. The research found that the more productive they are, the higher their ability to reframe, appreciate the positive, and see the future unfold from present. The research findings toward those with high productivity is a result of how long they have been attached to their commitment to be an entrepreneur so it leads them to get used to self-discipline and it demands them to have a good time management by planning, organizing, and prioritizing their activity. Suggestion for further research regarding this topic is to perform quantitative measurements to prove the relationship between Appreciative Intelligence and time management which affected to business success.